Fraudulent financial reporting in a nutshell / Noorain Omar - Omar, Noorain (Faculty of Accountancy, UiTM Kedah, 2019)
Fraudulent financial reporting can be defined as the intentional misrepresentation of a firm’s financial statements with the aim to give investors a mistaken impression about the firm’s operating performance and profitability. From the review of previous literatures, among the earliest definition of fraudulent financial reporting was defined by Elliot and Willingham (1980). According to them, fraudulent financial reporting is a deliberate fraud committed by management that injures investors and creditors through misleading financial statement. Approximately thirty decades later, Association of Certified Fraud Examiners (ACFE) (2008) described fraudulent financial reporting as “the intentional misstatement or omission of material information from the organization’s financial reports whereby fraudulent financial reporting cases often involve the reporting of fictitious revenues or the concealment of expenses or liabilities in order to make an organization appear more profitable than it really is. (p. 10)